About Tell Tweini (Syria) : artefacts, ecofacts and landscape : research results of the Belgian mission - Bretschneider, Joachim; Jans, Greta; Baeteman, Cecile; Boschloos, Vanessa; De Cupere, Bea; Degryse, Patrick; Hameeuw, Hendrik; Hirschfeld, Nicolle; Linseele, Veerle; Marinova, Elena (Botanist); Neer, W. van; Nys, Karin; et al. (Orientalia Lovaniensia analecta ;, 2019)
Tell Tweini or ancient Gibala is located in the Syrian coastal plain and represents the southernmost harbour of the Ugaritic Kingdom in the Late Bronze Age. As one of the few sites under excavation in the Northern Levant with a full archaeological sequence spanning the Early Bronze Age IV (ca. 2400 BCE) up to the Iron Age III period (ca. 500 BCE), Tell Tweini (Field A) is a key site for the study of the developments in the Northern Levant especially where the Bronze to Iron Age transition is concerned.0The yearly missions at Tell Tweini conducted by a Belgian-Syrian team have halted since 2011; however, the continuous research of the prodigious amount of data available has not. Over the past years the research team headed by Joachim Bretschneider (University Ghent) has focused on the study of particular groups of artefacts, ecofacts and landscape, resulting in new and exciting insights on various aspects of the settlement of Tell Tweini presented in this book.